Types of Expressive Illocutionary Acts Found in the Movie “True Spirit” By Sarah Spillane - Mete, Novita Serianna; Winarta, Ida Bagus Gde Nova (STKIP AGAMA HINDU SINGARAJA, 2024)
This study was aimed to analyze the types of expressive illocutionary acts found in the movie “True Spirit